Enfermedades Infecciosas y Parasitarias Presentes en Porcinos en la Provincia de Chimborazo - Chiliquinga Quinchiguano, Roberto Danilo (2017)
The prevalence of major infectious and parasitic diseases in pigs at Chimborazo Province during 2010-2015 period was obtained from primary sources such as AGROCALIDAD (Ministry of Agriculture, Livestock, Aquaculture and Fisheries), OIE (World Health Organization Animal) and primary research published between 2010 and 2015 resulting in the prevalence of Classical Swine Pest in 2010 with 0.169%, 2012 0.14%, 2013 0.18%, 2014 0.078%, 2015 0.89%; the prevalence of Porcine Epidemic Diarrhea in 2012 with 0.30%; the prevalence of Mycoplasma in the year 2012 with 0.30%, while in 2011 no case was recorded, so the prevalence is 0, which are the main infectious diseases that were found at Chimborazo Province among the years investigated ; with regard to parasitic diseases there is no research carried out so the Community of Maldonado,Riobamba Canton, Chimborazo Province,was selected to determinate gastrointestinal parasites with a sample of 200 animals from a total population of 264, each animal was performed acoprological examination to determine the presence of parasite eggs in the faeces. The presence of parasites such as Oesophagostomumspp with 31%, Coccidia with 30%, Hyostrongylus with 17% and Trichuris with 22% were found in a general way, through the laboratory analysis carried out in July 2017 in the laboratories of the Technical University of Cotopaxi.